The legislative framework of donor human milk and human milk banking in Europe - Daniel Klotz; Aleksandra Wesołowska; Enrico Bertino; Guido E. Moro; Jean‐Charles Picaud; Antoni Gayà; Gillian Weaver (Wiley, 2022)
Abstract Data about the regulatory approaches to donor human milk (DHM) in European countries are lacking. The aim of this study is to describe the various regulations of DHM within European countries, to assess its legislative context and its impact in relation to donor milk banking. We performed a cross‐sectional survey using a semistructured online questionnaire addressing 29 national European milk‐banking representatives from June 2020 to February 2021. Representatives of 26 national DHM services participated in this study. The legal classification and regulatory status of DHM were defined in 9 out of 26 areas of jurisdiction (35%) as either food product (n = 6), product of human origin according to a blood, tissue, cell regulation (n = 2), or medicinal product (n = 1). In the remainder, DHM remains unclassified. Most legislations did not provide a comprehensive framework concerning DHM and costs to cover milk bank operations were rarely reimbursed. In general, the lack of national legislative governance and the actual legislative regulations in place do not support the use of DHM in European countries. National medical guidelines for the use of DHM have been issued in only 11 countries. The current number and distribution of milk banks (n = 239) within participating countries may not provide an equitable access to DHM for eligible infants. These findings could guide stakeholders aiming to establish a regulatory framework for DHM.